Extended generalized octagons and the group He - Pasechnik, Dmitrii V. (2013)
Let Γ be an extended generalized octagon such that the points of a triple {u, v, w} not on a block are pairwise adjacent if and only if the distance betweenv andw in the local generalized octagon Γu equals 3 and there is a thick line through any point of Γu. Then Γ is one of the two examples related to the groups 2·L3(4).22 and He. It is also shown that Γ does not admit further extensions.